A novel ionic AIE smart responsive material with multiple structural transformations. Issue 34 (14th June 2021) - Xu, Zixuan; Su, Linhan; Chen, Xiaofen; Yang, Ying
Abstract : A novel ionic AIE smart responsive material [TPE-Dim-DMe] (Br)2 and its multiple applicaitions. Abstract : A novel ionic liquid [TPE-Dim-DMe] (Br)2 was successfully synthesiszed. With the change of temperature, quadruple transformations of structure were observed in the [TPE-Dim-DMe] (Br)2 crystal, and it simultaneously displayed mechanochromic phenomena. In addition, its excellent solubility in water makes it a novel bioimaging agent.